Genetic Analysis Reveals a Longevity-Associated Protein Modulating Endothelial Function and Angiogenesis. Issue 4 (31st July 2015) - Villa, Francesco; Carrizzo, Albino; Spinelli, Chiara C.; Ferrario, Anna; Malovini, Alberto; Maciąg, Anna; Damato, Antonio; Auricchio, Alberto; Spinetti, Gaia; Sangalli, Elena; Dang, Zexu; Madonna, Michele; et al.
<x xml:space="preserve">Abstract</x> Rationale: Long living individuals show delay of aging, which is characterized by the progressive loss of cardiovascular homeostasis, along with reduced endothelial nitric oxide synthase activity, endothelial dysfunction, and impairment of tissue repair after ischemic injury. Objective: Exploit genetic analysis of long living individuals to reveal master molecular regulators of physiological aging and new targets for treatment of cardiovascular disease. Methods and Results: We show that the polymorphic variant rs2070325 (Ile229Val) in bactericidal/permeability-increasing fold-containing-family-B-member-4 (BPIFB4) associates with exceptional longevity, under a recessive genetic model, in 3 independent populations. Moreover, the expression of BPIFB4 is instrumental to maintenance of cellular and vascular homeostasis through regulation of protein synthesis. BPIFB4 phosphorylation/activation by protein-kinase-R–like endoplasmic reticulum kinase induces its complexing with 14-3-3 and heat shock protein 90, which is facilitated by the longevity-associated variant. In isolated vessels, BPIFB4 is upregulated by mechanical stress, and its knock-down inhibits endothelium-dependent vasorelaxation. In hypertensive rats and old mice, gene transfer of longevity-associated variant-BPIFB4 restores endothelial nitric oxide synthase signaling, rescues endothelial dysfunction, and reduces blood pressure levels. Furthermore, BPIFB4 is implicated in vascular repair. BPIFB4 is abundantly expressed in circulating CD34+ cells of long living individuals, and its knock-down in endothelial progenitor cells precludes their capacity to migrate toward the chemoattractant SDF-1. In a murine model of peripheral ischemia, systemic gene therapy with longevity-associated variant-BPIFB4 promotes the recruitment of hematopoietic stem cells, reparative vascularization, and reperfusion of the ischemic muscle. Conclusions: Longevity-associated variant-BPIFB4 may represent a novel therapeutic tool to fight endothelial dysfunction and promote vascular reparative processes.